The value of low-intensity pulsed ultrasound in reducing ovarian injury caused by chemotherapy in mice - Yi Zhou; Fengyu Zhu; Yuanyuan Zhou; Xuqing Li; Shuhan Zhao; Yiqing Zhang; Ying Zhu; Hongyan Li; Yunxia Cao; Chaoxue Zhang (BMC, 2024)
Abstract Background Ovarian damage and follicle loss are major side effects of chemotherapy in young female patients with cancer. However, effective strategies to prevent these injuries are still lacking. The purpose of this study was to verify low-intensity pulsed ultrasound (LIPUS) can reduce ovarian injury caused by chemotherapy and to explore its underlying mechanisms in mice model. Methods The mice were randomly divided into the Control group, Cisplatin group, and Cisplatin + LIPUS group. The Cisplatin group and Cisplatin + LIPUS group were intraperitoneally injected with cisplatin every other day for a total of 10 injections, and the Control group was injected with saline. On the second day of each injection, the Cisplatin + LIPUS group received irradiation, whereas the other two groups received sham irradiation. We used a variety of biotechnologies to detect the differences in follicle count, granulosa cell apoptosis, fibrosis, transcriptome level, oxidative damage, and inflammation in differently treated mice. Result LIPUS was able to reduce primordial follicle pool depletion induced by cisplatin and inhibit the apoptosis of granulosa cells. Transcriptomic results confirmed that LIPUS can reduce ovarian tissue injury. We demonstrated that LIPUS can relieve ovarian fibrosis by inhibiting TGF-β1/Smads pathway. Meanwhile, it can reduce the oxidative damage and reduced the mRNA levels of proinflammatory cytokines caused by chemotherapy. Conclusion LIPUS can reduce the toxic effects of chemotherapy drugs on ovaries, inhibit ovarian fibrosis, reduce the inflammatory response, and redcue the oxidative damage, reduce follicle depletion and to maintain the number of follicle pools.